2008
DOI: 10.1016/j.clim.2008.03.522
|View full text |Cite
|
Sign up to set email alerts
|

Monosomy 1p36 uncovers a role for OX40 in survival of activated CD4+ T cells

Abstract: Monosomy 1p36 is a subtelomeric deletion syndrome associated with congenital anomalies presumably due to haploinsufficiency of multiple genes. Although immunodeficiency has not been reported, genes encoding costimulatory molecules of the TNF receptor superfamily (TNFRSF) are within 1p36 and may be affected. In one patient with monosomy 1p36, comparative genome hybridization and fluorescence in-situ hybridization confirmed that TNFRSF member OX40 was included within the subtelomeric deletion. T cells from this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Suhoski et al reported that the genes undergoing deletion by 1p36 microdeletion encode the costimulatory molecules of the TNF receptor superfamily (TNFRSF) [15]. However, primary immunodeficiency due to 1p36 deletion has not yet been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Suhoski et al reported that the genes undergoing deletion by 1p36 microdeletion encode the costimulatory molecules of the TNF receptor superfamily (TNFRSF) [15]. However, primary immunodeficiency due to 1p36 deletion has not yet been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Membrane type ligand OX40L interacts with membranetype OX40 to mediate activation, quantity expansion, transportation, and life expansion of CD4+ T cells, as well as, to promote the formation of germinal centers and the maturation of DCs. [18][19][20][21] The interactions of OX40/OX40L have been found to play a critical role in the development of many infl ammatory and autoimmune diseases. 22,23 Some studies 24,25 found that many asthmatic responses were not induced in OX40L-defi cient BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%